Anti-corrosion and wear-resistant rotating guide pushing block and preparation method thereof

CN122919310APending Publication Date: 2026-10-16SOUTHWEST PETROLEUM UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611361306.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]有鉴于此,本发明的目的在于提供一种防腐耐磨旋转导向推靠块及其制备方法,以解决推靠块耐磨防腐性能差、更换成本高等缺点

Benefits of technology

(1)采用激光熔覆工艺在可拆卸耐磨工作块工作面制备仿生点线交错熔覆层,降低热影响,避免形成热应力;通过添加稀土氧化物粉末提高耐腐蚀性能,增强熔覆层与工作块表面之间的结合力,提升服役寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122919310A_ABST
    Figure CN122919310A_ABST
Patent Text Reader

Abstract

The application discloses a kind of anticorrosive wear-resistant rotary steering push block and preparation method thereof, belong to rotary steering system parts field.The anticorrosive wear-resistant rotary steering push block includes push block base body and detachable wear-resistant working block;The detachable wear-resistant working block is positioned between push block base body by dovetail tenon groove, and realizes detachable connection by cooperating end locking bolt;The working surface of the detachable wear-resistant working block is a layer of bionic point line staggered anticorrosive wear-resistant cladding layer.Point line staggered bionic structure is prepared by laser cladding, and special geometric arrangement can disperse contact stress and slow down single-point wear;Protrusion reduces contact area with well wall, which is beneficial to drilling fluid circulation, strengthens heat dissipation, reduces frictional resistance and medium retention corrosion.Push block base body and wear-resistant working block are positioned by dovetail tenon, bolt locking detachable assembly, and only wear-resistant block is replaced after wear, which saves material consumption and reduces drilling operation and maintenance cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of rotary guide system components, specifically relating to a corrosion-resistant and wear-resistant rotary guide push block and its preparation method. Background Technology

[0002] Rotary steering systems are the core equipment for directional drilling in modern drilling engineering. Based on their steering principles, they can be divided into push-type and directional types. Among them, the push-type rotary steering system relies on the push block to act directly on the well wall, generating a lateral pushing force to change the drilling direction of the drill bit. It has the advantages of relatively simple structure, fast response speed, and high build-up rate, and is widely used in complex structure wells, extended reach wells, and deepwater oil and gas reservoir development.

[0003] However, in harsh downhole environments, the push block is subjected to severe abrasion from the wellbore and cuttings, impact loads, and corrosion from media such as oxygen and chloride ions, making it prone to corrosion and wear failure. Traditional integral push blocks require complete replacement after failure, resulting in high maintenance costs. Existing surface strengthening technologies such as coatings, plating, and patches cannot simultaneously achieve high wear resistance, strong corrosion resistance, high bonding strength, and impact resistance, making it difficult to meet the long-term service requirements of deep wells and complex formations, and subsequent repairs are also difficult. Summary of the Invention

[0004] In view of this, the purpose of the present invention is to provide a corrosion-resistant and wear-resistant rotary guide push block and its preparation method, so as to solve the shortcomings of poor wear resistance and corrosion resistance and high replacement cost of the push block.

[0005] To achieve the above objectives, the present invention provides a corrosion-resistant and wear-resistant rotary guide push block, which includes a push base and a detachable wear-resistant working block; the detachable wear-resistant working block is positioned with the push base by a dovetail tenon and is detachably connected with an end locking bolt; the working surface of the detachable wear-resistant working block is a biomimetic dotted line interlaced corrosion-resistant and wear-resistant cladding layer.

[0006] Furthermore, the biomimetic dot-line interlaced anti-corrosion and wear-resistant cladding layer consists of alternating rows of cylindrical protrusions and elongated hemispherical protrusion cladding bands. The height H of the cylindrical protrusions in the rows of cylindrical protrusions is 3-5 mm, and the diameter φ1 is 2H; the spacing S1 is 6H. The diameter of the elongated hemispherical protrusion cladding band is φ2, and φ2 = φ1. Multi-pass overlapping scanning is used for forming, with an overlap rate of 40%-50%. The overlap rate is defined as the percentage of the lateral overlap width of adjacent single-pass cladding to the total width of the single-pass cladding.

[0007] Furthermore, the angle α between the elongated hemispherical protrusion cladding band and the horizontal line is 45~90°, and the distance between the two elongated hemispherical protrusion cladding bands is S1; the row of cylindrical protrusions is located between the two elongated hemispherical protrusion cladding bands, and their arrangement is parallel to the cladding bands.

[0008] Furthermore, the detachable wear-resistant working block is positioned with the push base by a dovetail tenon. Specifically, the working surface of the push base has a dovetail tenon, which is vertical relative to the mounting surface of the push base. The spacing S2 between adjacent dovetail tenons is 30~50mm, the dovetail angle β is 50°~70°, the upper length L1 of the tenon is 10~15mm, and the height L2 of the tenon is 10~15mm. The bottom of the detachable wear-resistant working block is formed with a matching dovetail tenon, which slides into the assembly along the length of the dovetail tenon.

[0009] Furthermore, the locking bolts are 17-4PH stainless steel countersunk head bolts with specifications of M4~M6, and the threads are coated with anaerobic thread-locking agent.

[0010] Its beneficial effect is that the detachable wear-resistant working block can be removed and replaced separately after wear, without the need to replace the push base.

[0011] Furthermore, the biomimetic dotted and line interlaced anti-corrosion and wear-resistant cladding layer is prepared by laser cladding process from a composite powder containing nickel-based alloy, hard wear-resistant phase, corrosion-resistant phase and rare earth oxide.

[0012] Furthermore, the specific mass percentage of the composite powder is as follows: C powder: 0.2 wt%~0.5 wt%, Cr powder: 13 wt%~20 wt%, Mo powder: 3 wt%~5 wt%, B powder: 0.5 wt%~2 wt%, Fe powder: 5 wt%~7 wt%, W powder: 2.5 wt%~4 wt%, rare earth oxide CeO2 powder: 8 wt%~11 wt%, with the balance being Ni powder; and the particle size of the composite powder is 120-200 mesh, with a sphericity of 0.8~0.9.

[0013] Its beneficial effects are as follows: Ni, as the main matrix phase, has excellent corrosion resistance, while improving the toughness of the cladding layer and inhibiting crack initiation; CeO2 can refine grains, purify grain boundaries, reduce thermal stress of laser cladding, and improve corrosion and wear resistance; Cr and Mo synergistically form a dense passivation film, improving corrosion resistance, while generating a high-hardness wear-resistant phase; C and B react with metallic elements to generate a hard reinforcing phase, improving wear resistance; an appropriate amount of W can combine with elements such as C and Cr in the coating to precipitate highly stable hard carbides, improving the wear resistance of the cladding layer; adding an appropriate amount of Fe can reduce costs, while matching the thermal expansion coefficient of the matrix and reducing interfacial stress.

[0014] The present invention also provides a method for preparing the above-mentioned corrosion-resistant and wear-resistant rotary guide push block, comprising the following steps:

[0015] S1, processing and shaping The push-in base and the detachable wear-resistant working block are machined separately, with a surface roughness Ra≤1.6μm; S2, Powder preparation Take the composite powder raw materials in proportion, mix them evenly, and obtain the cladding layer composite powder; S3, Cleaning Preheating The surface of the detachable wear-resistant working block is ultrasonically cleaned. After cleaning, it is preheated to 150~200℃ and kept at that temperature for 1~2 hours. S4, Laser Cladding A biomimetic dot-line interlacing anti-corrosion and wear-resistant cladding layer was prepared on the surface of the wear-resistant working block using laser cladding equipment according to design parameters. S5, Assembly Locking Slide the detachable wear-resistant working block, which has been clad, into the push base along the dovetail groove coated with high-temperature grease, tighten the locking bolts, and the assembly is complete.

[0016] The laser cladding process parameters are as follows: laser power 1800~2200 W, scanning speed 1~1.5 mm / s, powder feeding rate 10~15 g / min, argon protection flow rate 15~20 L / min; after cladding, stress relief annealing is performed at 260~300℃, and the temperature is held for 2~4 h. After annealing, the furnace is cooled to room temperature.

[0017] In summary, this invention provides a corrosion-resistant and wear-resistant rotary guide push block and its preparation method. Compared with the prior art, this invention has the following significant advantages: (1) A biomimetic dot-line interlacing cladding layer is prepared on the working surface of the detachable wear-resistant working block using laser cladding technology to reduce the heat impact and avoid the formation of thermal stress; the corrosion resistance is improved by adding rare earth oxide powder, the bonding force between the cladding layer and the working block surface is enhanced, and the service life is improved.

[0018] (2) The biomimetic structure formed by laser cladding process is not only able to effectively disperse the huge contact stress during the working process through special geometric arrangement, reducing single-point wear; at the same time, the raised structure reduces the actual contact area with the well wall, and can promote the flow of drilling fluid, improve the frictional heat transfer of the push block, and reduce frictional resistance and the risk of corrosive media retention.

[0019] (3) The detachable connection structure is adopted. The push base and the detachable wear-resistant working block are positioned by dovetail groove and fixed by locking bolts. Disassembly and assembly are convenient. The wear-resistant working block can be replaced separately after wear without replacing the push base, which reduces material waste and lowers the maintenance and replacement costs during drilling. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0021] Figure 1 This is a schematic diagram of the anti-corrosion and wear-resistant rotary guide push block structure of the present invention; Figure 2 This is a front view of the corrosion-resistant and wear-resistant rotary guide push block of the present invention; Figure 3 This is a top view of the corrosion-resistant and wear-resistant rotary guide push block of the present invention; Figure 4 This is a schematic diagram of the push base structure in the corrosion-resistant and wear-resistant rotary guide push block of the present invention; Figure 5 This is a schematic diagram of the manufacturing process of the corrosion-resistant and wear-resistant rotary guide push block of the present invention.

[0022] In the diagram: 1. Push-back base, 2. Removable wear-resistant working block, 3. Bionic dotted and line interlaced anti-corrosion and wear-resistant cladding layer, 4. Straight cylindrical protrusion group, 5. Long strip hemispherical protrusion cladding band, 6. Dovetail tenon, 7. Locking bolt. Detailed Implementation

[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] The term "embodiment" used herein, as an example, is not necessarily construed as superior to or better than other embodiments. Performance testing in the embodiments of this application, unless otherwise specified, employs conventional testing methods in the art. It should be understood that the terminology used in this application is merely for describing particular implementations and is not intended to limit the scope of this disclosure. Unless otherwise stated, the technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; other experimental methods and technical means not specifically mentioned herein refer to experimental methods and technical means commonly used by one of ordinary skill in the art.

[0025] Except as described in this invention, it should be understood that the terms “middle,” “upper,” “lower,” “rise,” “fall,” “vertical,” “surface,” “top,” “bottom,” “inner,” and “outer,” etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limiting this invention.

[0026] To better illustrate the content of this application, numerous specific details are provided in the following detailed embodiments. Those skilled in the art should understand that this application can be implemented even without certain specific details. In the embodiments, some methods, means, instruments, and devices well-known to those skilled in the art are not described in detail in order to highlight the main points of this application.

[0027] Without conflict, the technical features disclosed in the embodiments of this application can be combined arbitrarily, and the resulting technical solution belongs to the content disclosed in the embodiments of this application.

[0028] Example 1 A corrosion-resistant and wear-resistant rotary guide push block, such as Figure 1 As shown, the corrosion-resistant and wear-resistant rotary guide push block includes a push base 1 and a detachable wear-resistant working block 2; the detachable wear-resistant working block 2 and the push base 1 are positioned by a dovetail tenon and groove and are detachably connected with the end locking bolt 7; the working surface of the detachable wear-resistant working block 2 is a layer of biomimetic dot-line interlaced corrosion-resistant and wear-resistant cladding layer 3.

[0029] The biomimetic dotted and line interlaced anti-corrosion and wear-resistant cladding layer is composed of alternating rows of cylindrical protrusions 4 and elongated hemispherical protrusion cladding strips 5; the height H of the cylindrical protrusions in the rows of cylindrical protrusions 4 is 3 mm, the diameter φ1 is 6 mm, the spacing S1 is 18 mm, and the diameter φ2 of the elongated hemispherical protrusion cladding strips 5 is 6 mm, with an overlap rate of 40%.

[0030] The angle α between the elongated hemispherical protrusion cladding band 5 and the horizontal line is 90°, and the distance S1 between the two elongated hemispherical protrusion cladding bands 5 is 18mm; the straight cylindrical protrusion group 4 is located between the two elongated hemispherical protrusion cladding bands 5, and the arrangement is parallel to the cladding bands.

[0031] The detachable wear-resistant working block 2 is positioned with the push base 1 by a dovetail tenon. Specifically, the working surface of the push base 1 is provided with a dovetail tenon 6, which is vertical relative to the mounting surface of the push base. The distance S2 between adjacent dovetail tenons 6 is 30mm, the dovetail angle β is 50°, the upper length L1 of the tenon is 10mm, and the height L2 of the tenon is 10mm. The bottom of the detachable wear-resistant working block is formed with a matching dovetail tenon, which slides into the assembly along the length of the dovetail tenon 6.

[0032] The locking bolt 7 is a 17-4PH stainless steel internal hexagon countersunk bolt, with specifications of M4~M6, and the threads are coated with anaerobic thread-locking agent.

[0033] The biomimetic dotted and line interlaced anti-corrosion and wear-resistant cladding layer 3 is prepared by laser cladding process from a composite powder containing nickel-based alloy, hard wear-resistant phase, corrosion-resistant phase and rare earth oxide.

[0034] Specifically, the composite powder has the following mass percentages: C powder: 0.2 wt%, Cr powder: 13 wt%, Mo powder: 3 wt%, B powder: 0.5 wt%, Fe powder: 5 wt%, W powder: 3 wt%, rare earth oxide CeO2 powder: 8 wt%, and the balance is Ni powder; and the composite powder has a particle size of 120 mesh and a sphericity of 0.8.

[0035] The preparation method of the above-mentioned corrosion-resistant and wear-resistant rotary guide push block includes the following steps: S1, processing and shaping The push-in base 1 and the detachable wear-resistant working block 2 are respectively machined and formed, with a surface roughness Ra≤1.6μm; S2, Powder preparation Take the composite powder raw materials in proportion, mix them evenly, and obtain the cladding layer composite powder; S3, Cleaning Preheating The surface of the detachable wear-resistant working block 2 is ultrasonically cleaned. After cleaning, it is preheated to 150℃ and kept at that temperature for 1 hour. S4, Laser Cladding A biomimetic dot-line interlacing anti-corrosion and wear-resistant cladding layer 3 was prepared on the surface of the wear-resistant working block using laser cladding equipment according to the design parameters. The laser cladding process parameters were: laser power 1800W, scanning speed 1 mm / s, powder feeding rate 10 g / min, and argon protection flow rate 15L / min. After cladding, the material was subjected to stress-relief annealing at 260℃ for 2 hours and then cooled to room temperature in the furnace.

[0036] S5, Assembly Locking Slide the detachable wear-resistant working block 2, which has been clad, into the base body 1 along the dovetail groove 6 coated with high-temperature grease, and tighten the locking bolt 7 to complete the assembly.

[0037] Comparative Example 1 Everything else is the same as in Example 1, except that the mass percentages of the composite powder are replaced as follows: C powder: 0.2 wt%, Cr powder: 13 wt%, Mo powder: 3 wt%, B powder: 0.5 wt%, W powder: 3 wt%, with the balance being Fe powder; the particle size is 120 mesh, and the sphericity is 0.8~0.9. Compared with Example 1, Ni and CeO2 are not added, and the balance is entirely Fe powder.

[0038] Comparative Example 2 Everything else is the same as in Example 1, except that laser cladding is not performed.

[0039] Performance testing Corrosion and wear resistance test Corrosion and wear verification tests were conducted on the push blocks in Example 1, Comparative Example 1, and Comparative Example 2, respectively. The specific steps are as follows: (1) Using wire cutting technology, samples were taken from the push blocks in Example 1, Comparative Example 1 and Comparative Example 2. All samples were cuboid samples (height 3mm, width 15mm, length 30mm). (2) Then, the sample was cleaned with acetone and ethanol in sequence. After cleaning, the sample was dried with cold air and then weighed for later use. (3) Place the prepared sample into the high temperature and high pressure corrosion and wear test apparatus, add the prepared 3.5%wt NaCl solution, then seal the high temperature and high pressure vessel and heat it to 50℃. The load during the test is 50N and the test time is 48h. (4) After the test, the sample was taken out and cleaned with film removal solution, deionized water and ethanol in sequence. After drying with cold air, the sample was weighed and the corrosion wear rate was calculated. Then, a stereomicroscope was used to observe whether there was any peeling or cracking on the sample surface.

[0040] The results are shown in Table 1.

[0041] Table 1. Corrosion and wear rates, cladding surface condition, and peeling and cracking of the push block samples in the examples.

[0042] As shown in Table 1, the average corrosion and wear rate of the push block samples with anti-corrosion and wear-resistant cladding coatings in the examples was much lower than that of the samples without cladding coatings, and no cladding or cracking was observed. Furthermore, the anti-corrosion and wear-resistant effect of the nickel-based alloy cladding coating containing rare earth elements was superior to that of the iron-based alloy cladding coating without rare earth elements.

[0043] The above tests demonstrate that the corrosion-resistant and wear-resistant rotary guide push block of the present invention has excellent corrosion-resistant and wear-resistant properties in oil and gas wells and can meet the application conditions.

[0044] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A corrosion-resistant and wear-resistant rotary guide push block, characterized in that, The corrosion-resistant and wear-resistant rotary guide push block includes a push base (1) and a detachable wear-resistant working block (2); the detachable wear-resistant working block (2) and the push base (1) are positioned by a dovetail tenon and groove and are detachably connected by an end locking bolt (7); The working surface of the detachable wear-resistant working block (2) is a layer of biomimetic dot-line interlaced anti-corrosion and wear-resistant cladding layer (3).

2. The corrosion-resistant and wear-resistant rotary guide push block according to claim 1, characterized in that, The biomimetic dot-line interlaced anti-corrosion and wear-resistant cladding layer is composed of alternating rows of cylindrical protrusions (4) and long strip-shaped hemispherical protrusion cladding strips (5); The height H of the cylindrical protrusions in the straight cylindrical protrusion group (4) is 3~5 mm, the diameter φ1 is 2H, and the spacing S1 is 6H; The elongated hemispherical protrusion cladding band (5) has a diameter of φ2, and φ2=φ1.

3. The corrosion-resistant and wear-resistant rotary guide push block according to claim 2, characterized in that, The angle α between the elongated hemispherical protrusion cladding band (5) and the horizontal line is 45~90°, and the distance between the two elongated hemispherical protrusion cladding bands (5) is S1; the straight cylindrical protrusion group (4) is located between the two elongated hemispherical protrusion cladding bands (5) and is arranged parallel to the cladding bands.

4. The corrosion-resistant and wear-resistant rotary guide push block according to claim 1, characterized in that, The detachable wear-resistant working block (2) is positioned with the push base (1) by a dovetail tenon, specifically: The working surface of the push base (1) is provided with a dovetail tenon (6). The dovetail tenon (6) is vertical relative to the mounting surface of the push base. The spacing S2 between adjacent dovetail tenons (6) is 30~50mm, the dovetail angle β is 50°~70°, the upper length L1 of the tenon is 10~15mm, and the height L2 of the tenon is 10~15mm. The bottom of the detachable wear-resistant working block is formed with matching dovetail tenons, which slide into the assembly along the length direction of the dovetail tenon (6).

5. The corrosion-resistant and wear-resistant rotary guide push block according to claim 1, characterized in that, The locking bolt (7) is a 17-4PH stainless steel internal hexagon countersunk bolt with a specification of M4~M6, and the threads are coated with anaerobic thread locking agent.

6. The corrosion-resistant and wear-resistant rotary guide push block according to claim 1, characterized in that, The biomimetic dotted and line interlaced anti-corrosion and wear-resistant cladding layer (3) is prepared by laser cladding process from a composite powder containing nickel-based alloy, hard wear-resistant phase, corrosion-resistant phase and rare earth oxide.

7. The corrosion-resistant and wear-resistant rotary guide push block according to claim 6, characterized in that, The specific mass percentages of the composite powder are as follows: C powder: 0.2 wt%~0.5 wt%, Cr powder: 13 wt%~20 wt%, Mo powder: 3 wt%~5 wt%, B powder: 0.5 wt%~2 wt%, Fe powder: 5 wt%~7 wt%, W powder: 2.5 wt%~4 wt%, rare earth oxide CeO2 powder: 8 wt%~11 wt%, with the balance being Ni powder; and the particle size of the composite powder is 120-200 mesh, with a sphericity of 0.8~0.

9.

8. A method for preparing the corrosion-resistant and wear-resistant rotary guide push block according to any one of claims 1 to 7, characterized in that, Includes the following steps: S1, processing and shaping The push-back base (1) and the detachable wear-resistant working block (2) are respectively machined and formed, with a surface roughness Ra≤1.6μm; S2, Powder preparation Take the composite powder raw materials in proportion, mix them evenly, and obtain the cladding layer composite powder; S3, Cleaning Preheating The surface of the detachable wear-resistant working block (2) is ultrasonically cleaned. After cleaning, it is preheated to 150~200℃ and kept warm for 1~2 hours. S4, Laser Cladding A biomimetic dot-line interlacing anti-corrosion and wear-resistant cladding layer was prepared on the surface of the wear-resistant working block using laser cladding equipment according to the design parameters (3). S5, Assembly Locking Slide the detachable wear-resistant working block (2) that has been clad into the push base (1) along the dovetail groove (6) coated with high-temperature grease, tighten the locking bolt (7), and complete the assembly.

9. The method for preparing the corrosion-resistant and wear-resistant rotary guide push block according to claim 8, characterized in that, The laser cladding process parameters are as follows: laser power 1800~2200 W, scanning speed 1~1.5 mm / s, powder feeding rate 10~15 g / min, argon protection flow rate 15~20 L / min; after cladding, stress-relief annealing is performed at 260~300℃, and the temperature is held for 2~4 h. After annealing, the furnace is cooled to room temperature.